Development of Interactive Multimedia for Indonesian Language Class VII SMPN 1 Gido - Kesaktian Telaumbanua; Riana; Hilda Natalia Hulu (RETORIKA: Jurnal Ilmu Bahasa, 2023)
The aim of this study is to create legitimate, usable, and efficient interactive multimedia learning tools. Research and development describes this sort of study. One such model that is utilized is the 4D model. For the creation of a wide range of educational materials, the 4D development model is an invaluable tool. There are four steps to the 4D process: defining, designing, developing, and disseminating. Interactive multimedia learning materials in the form of apps were created and tested in class VII-B at SMP Negeri 1 Gido using a validity testing stage that involved three validators, small group tests, and field tests. Interactive multimedia learning media in the form of apps has been validated by 97.5% of material and content experts, 100% of language experts, and 96.67% of design experts as valid and viable, according to the research. The questionnaire used to evaluate the practicality of application-based interactive multimedia learning material has a rating range from 1 to 4, with 4 being the most appropriate, 3 the most appropriate, 2 the least appropriate, and 1 the least appropriate. Applications using interactive multimedia learning materials that have been validated are considered viable for testing. In small group assessments, 86.67% of students found interactive multimedia learning materials to be practically applicable, while in field tests, 88.46% fell into the "very practical" category. A two-part student response questionnaire, administered in both small-group and field settings, was used to assess the usefulness of Indonesian language apps as interactive multimedia learning tools. With a percentage of classical completeness of 100% in the field test and an impressive 83.3% in the small group test, it is clear that learning mediums are highly successful. If the classical completeness in each trial is more than 80% with a very effective degree of efficacy, then learning is considered to grow. Research conducted by SMP Negeri 1 Gido in seventh grade using a 4D model to create an interactive multimedia learning tool that analyzes the language and structure of fables has been shown to be valid, practical, and successful.